The digitization of economic geography's infrastructure: Implications of the information overload. - Sánchez‐Hernández, José Luis (Geographical Journal, 2025)
During the last two decades, digitization has deeply transformed the 'infrastructure' of economic geography: the quantity and variety of available data, the techniques for retrieving and the tools for processing such data, and the practices of academic research. This commentary argues that the digitization process burdens economic geographers with an information overload, which is commonly addressed through various scholarly practices: coordinated research projects, direct technique‐based research design, and increasing participation in multidisciplinary research networks. However, both information overload and adaptive practices include a risk of fragmentation of the research community, since only large and/or well‐funded universities and research groups may adapt to the new research context depicted by the digitization of the 'infrastructure' of economic geography. Mixed methods and methodological polyglossia emerge, then, as a potential fix for pushing research ahead in economic geography. Digitization has transformed the 'infrastructure' of economic geography: the quantity and variety of available data, the techniques for retrieving and the tools for processing such data and the practices of academic research. Digitization burdens economic geographers with an information overload that encloses a risk of fragmentation of the research community, as only well‐funded research groups may adapt to the new research context. This fragmentation may be partially reduced by institutional changes focused on turning digitization into a driver of resource and skill transfer from the core to the periphery of economic geography.